A CORRELATION STUDY ON TEACHERS’ PERCEPTION OF THE SCHOOL CLIMATE AND THEIR DEGREE OF WORK MOTIVATION AT ASSUMPTION COLLEGE SAMUTPRAKARN, THAILAND - Melecio, Vanessa Kay; Vinitwatanakhun, Watana (Scholar: Human Sciences, 2022)
This study sought to examine the relationship between teachers’ perceptions of the school climate and their degree of work motivation at Assumption College Samutprakarn, Thailand. The study evaluated the teachers’ perceptions on the school’s climate as well as their degree of work motivation in which Means and Standard Deviations were used for quantitative analysis. Finally, the relationship between these two constructs were analysed through Pearson Product Moment Correlation Coefficient analysis. The study was conducted in the academic year of 2020 where 160 Thai teachers participated with the return rate of 91 percent from the total target population of 175. The result revealed that the teachers at Assumption College Samutprakarn had a relatively high perception and positive attitude towards the school climate. It also revealed that the teachers’ degree of work motivation on the basis of regulatory styles were relatively high on intrinsic (4.06), identified (4.15), and introjected (4.20). Furthermore, among the three recognized regulatory styles of motivation which had a high level of perception, introjected regulated type resulted to the highest mean score. However, they are moderately extrinsically motivated (3.42) as the data had shown. With regard to the study’s main purpose which was to examine the relationship between the teachers’ perception on the school climate and their work motivation, it revealed that the relationship between these two constructs were moderately positively correlated, r = .559, p < .05. The present study provided valuable information and extensive confirmation regarding the relationship between school climate and work motivation to which other researchers must further explore.